Professor L. D. Proskuriakov (1858 – 1926): A Chronological Retrospective of Life and Work - Salata, H. V. (History of science and technology, 2017)
This paper aims at identifying the key milestones in life and activities of the famous engineer in the field of structural mechanics professor Lavr Dmitrievich Proskuryakov (1858 – 1926). The author stresses that Proskuryakov’s contribution to the world science and techniques was not investigated properly.